2007
DOI: 10.1590/s0365-05962007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Freqüência de onicomicoses por leveduras em Maringá, Paraná, Brasil

Abstract: FUNDAMENTOS: Onicomicoses são afecções ungueais de origem infecciosa causadas por fungos e estão entre as principais onicopatias em todo o mundo. OBJETIVOS: Determinar a freqüência de leveduras como agentes etiológicos de onicomicoses na cidade de Maringá, PR, Brasil. MATERIAL E MÉTODOS: Realizou-se um estudo retrospectivo do período entre janeiro de 1997 e dezembro de 2004, em que foram avaliados os resultados de 1.295 pacientes com suspeita de onicomicose, recebidos no Laboratório de Ensino e Pesquisa em Aná… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
3
8
0
Order By: Relevance
“…According to statistical analysis by chi-square test, there is a significant difference between positive tests in both sexes. These data are consistent with the literature, as some authors have observed that the frequency of onychomycosis ranging from 67% to 74% in females ( Souza EAF et al , 2007 ; Effendy I et al , 2005 ; Alvarez MI et al , 2005 ; Koussidou T et al , 2002 ; Vélez A et al , 1997 ; Kemna ME and Elewski BE, 1996 ; Sais G et al , 1995 ; Schroeff J et al , 1992 ). Other authors found exactly the opposite, with about 64% of cases occurring in males ( Sarma S et al , 2008 ; Ghannoum MA et al , 2000 , Sigurgeirsson B and Steingrimsson O, 2000 ; Perea S et al , 2000 ).…”
Section: Discussionsupporting
confidence: 93%
“…According to statistical analysis by chi-square test, there is a significant difference between positive tests in both sexes. These data are consistent with the literature, as some authors have observed that the frequency of onychomycosis ranging from 67% to 74% in females ( Souza EAF et al , 2007 ; Effendy I et al , 2005 ; Alvarez MI et al , 2005 ; Koussidou T et al , 2002 ; Vélez A et al , 1997 ; Kemna ME and Elewski BE, 1996 ; Sais G et al , 1995 ; Schroeff J et al , 1992 ). Other authors found exactly the opposite, with about 64% of cases occurring in males ( Sarma S et al , 2008 ; Ghannoum MA et al , 2000 , Sigurgeirsson B and Steingrimsson O, 2000 ; Perea S et al , 2000 ).…”
Section: Discussionsupporting
confidence: 93%
“…A full 18% were negative, which can be attributed to the non-uniform distribution of fungi in nails, and also to the lack of proper orientation to the patient on how to proceed before the test completion. These results support those reported in the literature on the presence of Candida species as causative agents of onychomycosis, with C. albicans species described as prevalent in most works (Araujo et al 2003, Souza et al 2007, Brilhante et al 2005, including a study performed in João Pessoa-PB in 2002(Pontes et al 2002). However, this study, 1999-2010 from data analyzed demonstrated that C. tropicalis and C. krusei were the main yeasts causing Onychomycosis in João Pessoa during the last 11 years, emphasizing the importance of non-albicans Candida yeasts as causes of onychomycosis.…”
Section: Introductionsupporting
confidence: 88%
“…These three cases showed direct positive mycologic examination and the growth of the same agent in pure cultures in at least three tubes of Sabouraud dextrose agar. Similar to our study, Souza et al (21) reported 22 cases of Geotrichum candidum onychomycosis in Maringa, Brazil.…”
supporting
confidence: 91%